ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT STRESS MAHASISWA STATISTIKA UII TERHADAP PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 - Rahmi Novika Harahap; Marwah Nur Hakim; Apriyani Bella Thania; Edy Widodo (LPPM Universitas Bina Bangsa, 2021)
Covid-19 is a group of viruses that can spread very quickly, so every country must act to reduce the spread of Covid-19. The Ministry of Health of the Republic of Indonesia applies Health protocols to avoid crowds. It also leads to activities such as work and also studying from home to avoid physical contact. The Ministry of Education and Culture issued a circular regarding the implementation of online learning to spread Covid-19. Likewise, UII applies online knowledge. Changes in the learning system that are sudden and continue today can affect students' physical and mental health. Online learning and piles of assignments lead to increased anxiety and stress levels, even more so during the Covid-19 pandemic. This study aims to determine the factors that influence students' stress levels towards online learning. The method used is a survey method with a descriptive approach. Statistical data analysis used validity and reliability tests, univariate, bivariate, and multivariate. The results of the truth and reliability test showed that the Instrumen on DASS-42 was valid and reliable. Bivariate analysis with chi-square test found that there were differences in stress levels with age and semester. Multivariate analysis using an ordinal logistic regression test concluded that the factors that influence stress levels are age and male sex